2019
DOI: 10.3892/ijo.2019.4816
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated LRRK2 gene expression inhibits proliferation and migration while promoting the apoptosis of thyroid cancer cells by inhibiting activation of the JNK signaling pathway

Abstract: Emerging studies have indicated that leucine-rich repeat kinase 2 (LRRK2) is associated with thyroid cancer (TC). The present study investigated the effect of LRRK2 on the cell cycle and apoptosis in TC, and examined the underlying mechanisms in vitro . To screen TC-associated differentially expressed genes, gene expression microarray analysis was conducted. Retrieval of pathways associated with TC from the Kyoto Encyclopedia of Genes and Genomes database indicated that the c-Jun N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Moreover, they also confirmed that the down-regulation of LRRK2 in cultured tumor cells compromises MET activation and selectively reduces downstream MET signaling to mTOR and STAT3. Similarly, LRRK2 also showed anti-carcinogenic activities in the study by Jiang et al [37], which coincided with our analysis in LUAD. With the further exploration of LRRK2, it is noteworthy that LRRK2 CNV alteration showed high incidence and LRRK2 was correlated with various immune cells' infiltration levels, which provided multiple levels of evidence for the importance of LRRK2 in LUAD and also made LRRK2 more reliable as an independent prognostic signature.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, they also confirmed that the down-regulation of LRRK2 in cultured tumor cells compromises MET activation and selectively reduces downstream MET signaling to mTOR and STAT3. Similarly, LRRK2 also showed anti-carcinogenic activities in the study by Jiang et al [37], which coincided with our analysis in LUAD. With the further exploration of LRRK2, it is noteworthy that LRRK2 CNV alteration showed high incidence and LRRK2 was correlated with various immune cells' infiltration levels, which provided multiple levels of evidence for the importance of LRRK2 in LUAD and also made LRRK2 more reliable as an independent prognostic signature.…”
Section: Discussionsupporting
confidence: 92%
“…Emerging evidence suggests that LRRK2 mutations are highly related with cancers such as colon cancer and nonskin cancer 10,11 . Article also reported that LRRK2 is overexpressed in thyroid cancer 12 . Here, we noticed that in OC patients, LRRK2 high expression is associated with advanced clinical factors.…”
Section: Introductionsupporting
confidence: 52%
“…10,11 Article also reported that LRRK2 is overexpressed in thyroid cancer. 12 Here, we noticed that in OC patients, LRRK2 high expression is associated with advanced clinical factors. All the findings indicate that OCs expressing high levels of LRRK2 are more resistant to treatment potentially through promoting the HR pathway.…”
Section: Introductionmentioning
confidence: 89%
“…Lin et al identified a LINK-A lncRNA that mediated HIF1α phosphorylation at Ser797 by LRRK2, resulting in the activation of normoxic HIF1α signaling and promoting glycolysis reprogramming, tumorigenesis and progression in triple-negative breast cancer [ 33 ]. Jiang et al revealed that downregulated LRRK2 gene expression inhibited proliferation and migration while promoting the apoptosis of thyroid cancer cells by inhibiting activation of the JNK signaling pathway [ 34 ].…”
Section: Discussionmentioning
confidence: 99%